2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5947470
|View full text |Cite
|
Sign up to set email alerts
|

Talker-to-listener distance effects on the variations of the intensity and the fundamental frequency of speech

Abstract: In this study we focus on the relationship between the talker-tolistener distance (TLD) and the dynamics of speech intensity and fundamental frequency. A new experiment for the extraction of pertinent information from prosodic parameter variations for different TLDs is described. The proposed new recording protocol allows simulating a real TLD by using acoustically insulated rooms. We propose to measure the dynamics of f0 and intensity by using the variation between the minima and the maxima of their contours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…With regard to tone shape, our hypothesis is that the tone shapes corresponding to farther distances will be exaggerated, with high contrast, and those corresponding to close distances will be reduced, with low contrast . The acoustic landmarks representing tones at farther TLDs include high f0, delayed targets and steeper slopes (Fux et al, 2011;Xu & Wang, 2001;Xu, Xu, & Luo, 1999). 3.…”
Section: Introductionmentioning
confidence: 98%
“…With regard to tone shape, our hypothesis is that the tone shapes corresponding to farther distances will be exaggerated, with high contrast, and those corresponding to close distances will be reduced, with low contrast . The acoustic landmarks representing tones at farther TLDs include high f0, delayed targets and steeper slopes (Fux et al, 2011;Xu & Wang, 2001;Xu, Xu, & Luo, 1999). 3.…”
Section: Introductionmentioning
confidence: 98%
“…As distance increases so does the vocal effort. In fact, Brungart et al report that as distance doubles the intensity increases by 8 dB, while Liénard et al report that F0 increases at 3.5 Hz/dB (Fux et al, 2011) (Liénard and Di Benedetto, 1999). Distance, however, is not the only time we adjust our vocal effort.…”
Section: Vocal Effort Codingmentioning
confidence: 95%
“…Liénard and Di Benedetto (1999), however, also claim an increase in the second formant, F2, for females but this has not yet been widely accepted. Shouted sentences have increased initial F0 slope but a decreased final F0 (Fux et al, 2011) and a decreased spectral slope (Zhang and Hansen, 2007). They are longer in duration which is caused by longer word duration, but have a decreased silence duration (Zhang and Hansen, 2007).…”
Section: Vocal Effort Codingmentioning
confidence: 99%
“…We, however, refrained from replicating such a setting because of the known effects of talker-to-listener distance (henceforth TLD) on the variation of speech acoustics. It has been repeatedly shown that talkers spontaneously adjust their way of speaking in response to the increasing distance from the listeners, with consequences on various acoustic parameters, such as duration, intensity, fundamental frequency (f0) and formant frequencies (see a.o., Cheyne et al, 2009 ; Fux et al, 2011 ; Pelegrín-García et al, 2011 ). In this design, it would be hard to disentangle acoustic variations due to TLD and those to individualization or cooperation.…”
Section: Introductionmentioning
confidence: 99%